2018
DOI: 10.1111/pan.13446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remifentanil maintenance during recovery on emergence delirium in children with sevoflurane anesthesia

Abstract: Maintaining a low dose of remifentanil (0.05 μg/kg/min) throughout the recovery phase attenuated the incidence of emergence delirium in children undergoing strabismus surgery under sevoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Patients with persistent severe postoperative delirium have negative implications and experience less satisfaction, as do their families, due to the potential for self-injury and other injurious behaviors, being a burden on nursing staff. It has been shown that low-dose fentanyl (an induced dose of less than 1 µg/kg) used in children after sevoflurane-based anesthesia can reduce the incidence of emergence delirium without prolonged hospital stay [ 20 , 21 ] . Sufentanil, as a derivative of fentanyl, is a lipophilic opioid agonist that can easily pass through the blood-brain barrier and bind to plasma proteins at a higher rate than fentanyl [ 22 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with persistent severe postoperative delirium have negative implications and experience less satisfaction, as do their families, due to the potential for self-injury and other injurious behaviors, being a burden on nursing staff. It has been shown that low-dose fentanyl (an induced dose of less than 1 µg/kg) used in children after sevoflurane-based anesthesia can reduce the incidence of emergence delirium without prolonged hospital stay [ 20 , 21 ] . Sufentanil, as a derivative of fentanyl, is a lipophilic opioid agonist that can easily pass through the blood-brain barrier and bind to plasma proteins at a higher rate than fentanyl [ 22 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It is not easy to separate ED from pain-related agitation, as there is an overlap in the parameters assessing the two conditions. Therefore, the control of postoperative pain is highly recommended to reduce ED in pediatrics (14). In our study, two children in group I and one in group II needed rescue analgesics.…”
Section: Discussionmentioning
confidence: 70%
“…Remifentanil was administered until specific discharge criteria were met (modified Aldrete post-anesthesia recovery score > 9). The authors found a significant reduction of ED incidence using The Cole five-point scale (33.3% vs 68.3%; P = 0.002) and PAED scale for scores > 12 (5.1% vs 34.0%; P = 0.001), while length of stay in the PACU remained similar to the control group [33].…”
Section: Opioidsmentioning
confidence: 87%